Pendidikan di sebalik peristiwa israk dan mikraj: satu analisis kandungan kitab utama hadith - Jasmi, Kamarul Azmi (Pusat Pengkajian Kefahaman Ahli Sunnah Waljama'ah, Kolej Universiti Perguruan Agama Seri Begawan, 2014)
This article is .he outcome of a content analysis study of nine (Sunam Tiscah) hadith texts that are related to the Israk Mikraj event. The purposive sampling procedure is used to select the hadith; and 53 hadith have been chosen and recorded as verbatim data for analysis in Nvivo 7.0 in order to discover the theme, subthemes and other education-oriented subthemes of the Israk Mikraj incident. The findings reveal five most significant educational aspects arising from the event, with faith being the key thrust of the theme. These are followed by aspects Of good deeds to be practised by Muslims. bad deeds for them to refrain front, uniqueness of Prophet Muhammad and his ummah, and finally etiquette in Islam. An educational model of the Israk Mikraj event is also formulated to serve as a guide for the Muslim Ummah.